2020
DOI: 10.1021/acsomega.0c01822
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Aerobic Oxidation of Ethyl Lactate to Ethyl Pyruvate over V2O5/g-C3N4 Catalysts

Abstract: Graphitic carbon nitride (g-C3N4)-supported V2O5 catalysts were prepared by the impregnation pyrolysis method, and their physicochemical properties were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), Raman, X-ray photoelectron spectroscopy (XPS), UV–vis, TGA, N2 adsorption, and H2-TPR. These catalysts exhibit extremely high activity and selectivity in the aerobic oxidation of ethyl lactate to ethyl pyruvate. The excellent catalytic performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…As a typical magnetic material, Fe 3 O 4 has been widely used in the synthesis of magnetic photocatalysts due to its good stability, low cost, good magnetism, and environmental friendliness. In addition, it can also be used as a good redox medium to store electrons and further improve photocatalytic performance. …”
Section: Introductionmentioning
confidence: 99%
“…As a typical magnetic material, Fe 3 O 4 has been widely used in the synthesis of magnetic photocatalysts due to its good stability, low cost, good magnetism, and environmental friendliness. In addition, it can also be used as a good redox medium to store electrons and further improve photocatalytic performance. …”
Section: Introductionmentioning
confidence: 99%
“…the lower binding energy peak at 515.6 eV is ascribed to V 4+ and the higher one at 517.1 eV is assigned to V 5+ . 13,23,33 In general, metal elements with variable valence play a key role in oxidation reactions. Obviously, the percentage of V 4+ decreased with the increase of V loading.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…These by-products were also observed in earlier reports. 16,23 Moreover, the TOF is also listed in the last column of Table 2, which was calculated as moles of EL converted per moles of V per hour at 0.5 h for the V x O y /SBA-15 catalysts. The TOF was similar over the 0.5V x O y /SBA-15 and 0.9V x O y /SBA-15 catalysts, indicating that the dispersion of V on the catalyst surface was also similar.…”
Section: Catalytic Performancementioning
confidence: 99%
“…These transition metal-based catalysts showed an ethyl lactate conversion lower than 30% at 403 K in 3 h. The low activity for these transition metal-based catalysts with O 2 as oxidant would probably be attributed to high activation energy for O 2 at such a low temperature. 26 Yue et al 23 reported vanadia-supported graphitic carbon nitride (g-C 3 N 4 ) as an efficient catalyst in the liquid-phase oxidation of ethyl lactate to ethyl pyruvate. The turnover frequency of V 2 O 5 /g-C 3 N 4 is about an order of magnitude higher than that of the bulk V 2 O 5 , attributed to higher surface-chemisorbed oxygen species of V 2 O 5 /g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the free lactic acid, the alkyl lactates and pyruvates would be less reactive, and their ester functions could greatly lessen the competitiveness of the undesirable side reactions . Thus, alkyl lactates (methyl, ethyl, isopropyl, n -butyl) would be better feedstocks for the production of alkyl pyruvates, as they are more stable and can be easily converted to PA by the hydrolysis process. , Much work has consequently been conducted to investigate the selective oxidation reaction of alkyl lactates to alkyl pyruvates in the liquid phase or gas phase over Mo-based, ,,, V-based, , and Ti-based catalysts , using oxygen, , H 2 O 2 , , or tert -butyl hydroperoxide , as oxidants. The gas-phase oxidation was usually carried out at high temperature (>473 K) to get a relative high activity, but leading to a significant decrease in alkyl pyruvate selectivity, especially at high conversion. ,,,,, The liquid-phase oxidation could be realized under milder conditions (temperature <423 K, pressure <2 MPa) that make it possible to avoid over-oxidation reactions to get a high alkyl pyruvate selectivity (>90%) even at high alkyl lactate conversions.…”
Section: Introductionmentioning
confidence: 99%